Paracomesoma minor sp. n. and Microlaimus validus sp. n. (Nematoda) from the coast of Vietnam - Gagarin, Vladimir G.; Tu, Nguyen Dinh (Zootaxa, 2014)
Two nematode species isolated from sediments of the littoral zone of South China Sea on the coast of Vietnam are described and illustrated. Paracomesoma minor sp. n. is closely related to P. elegans Gagarin & Thanh, 2009 and P. lissum Gagarin & Thanh, 2009. It differs from the former species in the shorter body, longer and more slender tail, longer cephalic setae and shorter spicules, and from the latter species in the shorter body, longer cephalic setae, presence of cervical setae and smaller number of precloacal supplements in males. Microlaimus validus sp. n. is morphologically closest to M. citrus Gerlach, 1959 and M. nanus Blome, 1982 and differs from both species in the longer body, relatively shorter pharynx and relatively shorter and thicker tail.